Correlation between History of Diabetes Mellitus and Hypertension with Length of Hospitalization of Covid-19 Patients at Ummi Hospital Bogor and its Review according to Islamic View - Fitria Rahma; Titiek Djannatun; Firman Arifandi (Junior Medical Journal, 2022)
Introduction: COVID-19 is an infectious disease, has transmission through droplets and direct contact. COVID-19 patients who have comorbidities show a poorer prognosis. Based on data in Indonesia, the two most common comorbidities are hypertension (49.9%) and diabetes mellitus (36.9%). Death rates in diabetes mellitus and hypertension are the two highest in Indonesia with 9.4% (DM) and 9.2% (hypertension). Therefore, it is important to know the correlation between a history of diabetes mellitus and hypertension with the length of stay for COVID-19 patients from a medical and Islamic perspective.Method: This type of research is analytic observational with a case control research design. The study sample was all COVID-19 patients with a history of hypertension and diabetes mellitus who were hospitalized at the UMMI Bogor Hospital during the period January - June 2021 as many as 263 respondents. Data collection uses secondary data in the form of medical records. The analysis was carried out univariate and bivariate.Result: The results showed that 20 people (7.6%) had comorbid diabetes mellitus with an average length of stay of 15 days. Respondents with comorbid hypertension were 39 people (14.8%) with an average length of stay of 15 days. Meanwhile, respondents with complex comorbidities (hypertension and DM) were 22 people (8.4%) with an average length of stay of 22 days. Based on the results of the bivariate analysis using the Kruskal Wallis alternative test and the Post Hoc Turkey HSD test, a p-value of 0.000 (0.05) was obtained, then the p-value was smaller which indicated that H0 was rejected, meaning that there was a significant relationship between comorbidities and length of stay. hospitalization of COVID-19 patients.Conclusion: There is a significant relationship between a history of diabetes mellitus and hypertension with the length of stay of COVID-19 patients at Ummi Hospital, Bogor.